1999
DOI: 10.1016/s0002-9440(10)65134-6
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Genetic Aspects of Oligodendrogliomas Including Analysis by Comparative Genomic Hybridization

Abstract: Oligodendroglial neoplasms are a subgroup of gliomas with distinctive morphological characteristics. In the present study we have evaluated a series of these tumors to define their molecular profiles and to determine whether there is a relationship between molecular genetic parameters and histological pattern in this tumor type. Loss of heterozygosity (LOH) for 1p and 19q was seen in 17/23 (74%) well-differentiated oligodendrogliomas, in 18/23 (83%) anaplastic oligodendrogliomas, and in 3/8 (38%) oligoastrocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
143
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(157 citation statements)
references
References 16 publications
13
143
1
Order By: Relevance
“…Other series of oligodendroglial tumors investigated by CGH previously yielded imbalances on these chromosomes at similar frequencies. 20,[30][31][32][33][34][35] With respect to the prognostic significance of genetic alterations, previous reports have mostly focussed on 1p/19q deletions, which were found to be significantly associated with longer survival of patients with oligodendroglial tumors. 10,12,[14][15][16][17]36 In line with these data, we found that combined 1p and 19q losses were associated with a better prognosis in our patients (increase in median patient survival of around 70 months, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Other series of oligodendroglial tumors investigated by CGH previously yielded imbalances on these chromosomes at similar frequencies. 20,[30][31][32][33][34][35] With respect to the prognostic significance of genetic alterations, previous reports have mostly focussed on 1p/19q deletions, which were found to be significantly associated with longer survival of patients with oligodendroglial tumors. 10,12,[14][15][16][17]36 In line with these data, we found that combined 1p and 19q losses were associated with a better prognosis in our patients (increase in median patient survival of around 70 months, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Mixed OlAs were tumours in which the two cell populations with oligo-and astroglial phenotype were topographically separated, at least in some areas (Bigner et al, 1999); this definition basically corresponds to the biphasic OlAs in the WHO 2000 classification. Glioblastomas with oligodendroglial component (GOCs) (Bigner et al, 1999;Kleihues et al, 2002) were biphasic tumours with grade IV histological features.…”
Section: Histological Classification Of Gliomasmentioning
confidence: 99%
“…In an important next paper, Mainz et al showed that low-grade mixed oligoastrocytoma show either characteristic astrocytic lesions (TP53 mutations) or combined loss of 1p/19q, pointing out that at the molecular level mixed tumors do not exist [7]. Subsequent studies showed that anaplastic oligodendrogliomas showed in addition to 1p/19q loss other lesions (e.g., loss of 9p), but that typical genetic lesions found in glioblastoma were mutually exclusive with combined 1p/19q loss [8,9]. This pointed toward a glioblastoma-like genetic background of many anaplastic mixed oligoastrocytomas, further emphasizing that true mixed oligoastrocytic tumors do not exist.…”
Section: Oligodendroglioma: the Chemotherapy Sensitive Gliomamentioning
confidence: 99%